Daya Tarik Pahlawan Street Centre Sebagai Destinasi Wisata Kota Madiun - Muhyiddin Aziz; Ridho Muarief (Politeknik Negeri Madiun, 2022)
Attraction plays an important role in attracting tourist visits to a tourist destination. A city is often visited by people from outside the area for business or other reasons. If the city has a tourist destination that has its own charm, it can trigger tourist interest for people who come to the city and can advance the tourism sector. Therefore, this study was conducted to determine the attractiveness of Pahlawan Street Center as a tourist destination in Madiun City. The research was conducted using a qualitative descriptive method with data sources obtained from interviews and observations. Validity test is done by triangulation of techniques and sources. The results showed that Pahlawan Street Center has an attraction as a tourist destination because there is an interesting view and atmosphere, tourists can do fun things and tourists can shop there.